Pediatric Contractures in Burn Injury: A Burn Model System National Database Study. Issue 1 (January 2017) - Goverman, Jeremy; Mathews, Katie; Goldstein, Richard; Holavanahalli, Radha; Kowalske, Karen; Esselman, Peter; Gibran, Nicole; Suman, Oscar; Herndon, David; Ryan, Colleen M.; Schneider, Jeffrey C.
Abstract : Joint contractures are a major cause of morbidity and functional deficit. The incidence of postburn contractures and their associated risk factors in the pediatric population has not yet been reported. This study examines the incidence and severity of contractures in a large, multicenter, pediatric burn population. Associated risk factors for the development of contractures are determined. Data from the National Institute on Disability and Rehabilitation Research Burn Model System database, for pediatric (younger than 18 years) burn survivors from 1994 to 2003, were analyzed. Demographic and medical data were collected on each subject. The primary outcome measures included the presence of contractures, number of contractures per patient, and severity of contractures at each of nine locations (shoulder, elbow, hip, knee, ankle, wrist, neck, lumbar, and thoracic) at time of hospital discharge. Regression analysis was performed to determine predictors of the presence, severity, and numbers of contractures, with P < .05 used for statistical significance. Of the 1031 study patients, 237 (23%) developed at least 1 contracture at hospital discharge. Among those with at least one contracture, the mean was three (3.3) contractures per person. The shoulder was the most frequently contracted joint (27.9%), followed by the elbow (17.6%), wrist (14.2%), knee (13.3%), and ankle (11.9%). Most contractures were mild (38.5%) or moderate (36.3%) in severity. The statistically significant predictors of contracture development were age and intensive care unit (ICU) length of stay. The statistically significant predictors of severity of contracture were age, ICU length of stay, presence of amputation, and black race. Predictors of the number of contractures included total age, length of stay, length of ICU stay, presence of amputation, TBSA burned, and TBSA grafted. This is the first study to report the epidemiology of postburn contractures in the pediatric population. Approximately one quarter of children with a major burn injury developed a contracture at hospital discharge, and this could potentially increase as the child grows. Contractures develop despite early therapeutic interventions such as positioning and splinting; therefore, it is essential that we identify novel and more effective prevention strategies. Abstract : Supplemental Digital Content is available in the text.